THE MECHANISM OF EVALUATION OF ENVIRONMENTAL DAMAGE OF PRODUCTION - V. N. Egorov; M. V. Chernova (Стратегические решения и риск-менеджмент)
The ecological factor always has a negative impact on the profit of enterprises and creates a threat of crisis situations. The article presents the evaluation mechanism of permanent and emergency environmental damage caused by industrial activity. Measures of reduction of environmental risks and of prevention of crisis phenomena in the environmental subsystem are proposed.